Police Officers’ Ability in Recognizing Relevant Mental Health Conditions - Wittmann, Linus; Groen, Gunter; Hampel, Petra; Petersen, Ronja; Jörns-Presentati, Astrid (Frontiers in Psychology, 2021)
The recognition of certain mental health conditions is important as this requires police officers to communicate and behave in an adjusted manner with affected individuals. The objective of the present study was to test police officers’ knowledge about mental health symptoms as a component of their mental health literacy (MHL) and to examine if police officers’ perceived knowledge corresponds with their actual knowledge. A questionnaire was used to assess for MHL representing mental health conditions which occur frequently in police requests (schizophrenia, bipolar disorder, depression, post-traumatic stress disorders, and emotionally unstable personality disorder). Furthermore, the questionnaire assessed the frequency of police requests, the officers’ perceived knowledge regarding mental disorders and their sense of feeling sufficiently trained to deal with these kinds of requests. Eighty-two police officers participated in the study. Police officers’ actual knowledge about mental health conditions did not correspond with their perceived knowledge. Participants revealed a moderately high level of overall knowledge which differed with regard to symptoms of each of the five mental health conditions. The mental status of a paranoid schizophrenia was best identified by the police officers and the majority correctly allocated the symptoms. Post-traumatic stress disorders and manic episodes were only identified by a minority of police offers. Police training geared to prepare for requests involving individuals with mental disorders should expand this limited knowledge transfer and focus on a broader variety of mental health conditions that police officers frequently encounter in requests.